IDENTIFIKASI MODAL, PROFITABILITAS, LIKUIDITAS, PDB, INFLASI DAN NILAI TUKAR SEBAGAI PREDIKSI KRISIS PERBANKAN DI INDONESIA - BUDIARTI, WULAN (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: This study aims to determine the effect of capital, profitability, liquidity, Gross Domestic Product (GDP), inflation, and exchange rate to the prediction of banking crises in Indonesia during 2008-2012. Measurement conditions of crisis, namely BSF index method (Banking Sector Fragility) index. Samples taken in this study consisted of 18 commercial banks listed on the Indonesian Stock Exchange (IDX). The results showed that all the variables simultaneously significant to the prediction of banking crisis. Partially profitability and exchange rate have significant effect to the prediction of banking crisis. While capital, liquidity, GDP, and inflation does not significantly influence to the prediction of banking crisis. Keywords:banking crisis, BSF index, capital, profitability, liquidity,GDP,inflation, exchange rate and logistic regression.